Distributive Justice’s Direct And Indirect Linkages To Turnover Intention: A Structural Equation Modelling Approach - Ahmad Rafeein Mohamad; Kalsom Ali; Khairunneezam Mohd Noor (Unimas Publisher, 2026)
Indexed by WOS / SCOPUS / MYCITE